2021
DOI: 10.1126/scitranslmed.aaz6314
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming lipid metabolism prevents effector T cell senescence and enhances tumor immunotherapy

Abstract: The functional state of T cells is a key determinant for effective antitumor immunity and immunotherapy. Cellular metabolism, including lipid metabolism, controls T cell differentiation, survival, and effector functions. Here, we report that development of T cell senescence driven by both malignant tumor cells and regulatory T cells is a general feature in cancers. Senescent T cells have active glucose metabolism but exhibit unbalanced lipid metabolism. This unbalanced lipid metabolism results in changes of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 69 publications
5
124
0
Order By: Relevance
“… 278 , 279 , 280 , 281 , 282 Besides, elevated lipid metabolism and glucose/amino acid dearth also increase the production of reactive ROS and suppressive epigenetic modifications in T cells. 280 , 283 The metabolic characteristics of TME could further damage antitumor immunity and accelerate malignant progression. Moreover, obesity and other diseases caused by metabolism dysregulation are accompanied by inflammation to different degrees, which may induce a tendency toward tumor development if the inflammation exists for a long time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 278 , 279 , 280 , 281 , 282 Besides, elevated lipid metabolism and glucose/amino acid dearth also increase the production of reactive ROS and suppressive epigenetic modifications in T cells. 280 , 283 The metabolic characteristics of TME could further damage antitumor immunity and accelerate malignant progression. Moreover, obesity and other diseases caused by metabolism dysregulation are accompanied by inflammation to different degrees, which may induce a tendency toward tumor development if the inflammation exists for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the metabolic demands of tumors lead to severe dysfunction and abnormal differentiation in cytotoxic immune cells, including T cells and NK cells, which principally use glucose by glycolysis and mitochondrial oxidative phosphorylation 278–282 . Besides, elevated lipid metabolism and glucose/amino acid dearth also increase the production of reactive ROS and suppressive epigenetic modifications in T cells 280,283 . The metabolic characteristics of TME could further damage antitumor immunity and accelerate malignant progression.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tumor role of T cells may be enhanced by cholesterol; however, its role is negatively regulated by liver X receptors in the oxysterol-abundant TM ( Matsushita et al, 2021 ). A recent study demonstrated that lipid metabolism reprograming, triggered by the unbalanced lipid metabolism in senescent T cells, prevented the senescence of effector T cells ( Liu X. et al, 2021 ) and enhanced the functional specialization of regulatory T cells in cancers ( Lim et al, 2021 ). Lipid accumulation in the dendritic cells damaged their anti-tumor functions, as the affected cells could not effectively present tumor-associated antigens ( Herber et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported an association between lipid metabolism and T-cell senescence, suggesting that reprogrammed lipid metabolism was triggered by the upregulation of PLA2G4A in cancer cells and regulatory T-cells. Using melanoma and breast cancer in vivo models, they demonstrated enhanced therapeutic efficacy following inhibition of PLA2G4A [82]. Moreover, another study identified the negative correlation between response to tumor-infiltrating lymphocyte (TIL) therapy and upregulation of Sirt2 in human TILs.…”
Section: Target Discoverymentioning
confidence: 99%